A NOVEL PROTOCOL DESIGN TO EVALUATE THE PREVENTIVE/ PROPHYLACTIC PROPERTY OF DRUGS/ PLANT PRODUCTS/ NEUTRACEUTICALS AGAINST EXPERIMENTALLY INDUCED IABETES IN ANIMAL MODELS - SURESHA R.N; SUSHMA V NAIDU; SATISH A M; KALABHARATHI H L; PUSHPA V H (International Journal of Pharma and Bio Sciences, 2013)
To establish a novel methodology for the evaluation of prophylactic property of drugs/ plant products against experimentally induced diabetes in animal models. Test drug is administered by oral/ i.v. route to animals every day for 90 days. On 91st day, diabetes is induced by chemical method. Test drug administration is continued for another 4 days i.e. from 91st to 94th day. CBG, lipid profile, body weight are measured once in 15 days till 90 days and everyday for next 10 days by any standard method. After 3rd day of diabetes induction, test rats are not given any drugs, but regular feed is continued upto 10th day. CBG is recorded on 2nd/3rd day after diabetes induction and analysed as:If average CBG/ lipid levels in the test group is :- i)Same or more compared to the diabetic control group: infers that there is no prophylactic activity of the evaluating product. ii) Less than the diabetic control group: infers that the test evaluating product has antihyperglycemic activity indicating the possibility of prophylactic property. ii) Less than the non-diabetic control group at any time of the experiment (1st to 94th day): infers that the evaluating product has a positive tendency of hypoglycemia with possibility of treatment property. This novel methodology of investigating a drug for its prophylactic property against chemically induced diabetes in animal models may be useful to evaluate a product with future perspective targeting preventive approach in prediabetics or high risk individuals of type 2 diabetes and normal individuals. This novel approach may be useful to screen drugs / plant products / neutraceuticals likely to postpone onset of diabetes or development of its complications.